2017
DOI: 10.1021/acs.est.6b05711
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxygen Functionalities in Graphene Oxide Architectural Laminate Subnanometer Spacing and Water Transport

Abstract: Active research in nanotechnology contemplates the use of nanomaterials for environmental engineering applications. However, a primary challenge is understanding the effects of nanomaterial properties on industrial device performance and translating unique nanoscale properties to the macroscale. One emerging example consists of graphene oxide (GO) membranes for separation processes. Thus, here we investigate how individual GO properties can impact GO membrane characteristics and water permeability. GO chemistr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 70 publications
5
53
0
Order By: Relevance
“…The enlarged channels in turn let more water molecules to fill in and aggregate from discreet patches into continuous monolayer that quickly passed through the laminates. On the contrary, the water transport slows down if GO membranes are reduced by thermal, chemical, and UV irradiation treatments . During the reduction, oxygen‐containing functionalities, once acting as the spacers of the channels, are eliminated to cause tightened capillaries ( d ‐spacing below 4 Å) that prevent water from being soaked in.…”
Section: Transport‐controlling Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enlarged channels in turn let more water molecules to fill in and aggregate from discreet patches into continuous monolayer that quickly passed through the laminates. On the contrary, the water transport slows down if GO membranes are reduced by thermal, chemical, and UV irradiation treatments . During the reduction, oxygen‐containing functionalities, once acting as the spacers of the channels, are eliminated to cause tightened capillaries ( d ‐spacing below 4 Å) that prevent water from being soaked in.…”
Section: Transport‐controlling Effectsmentioning
confidence: 99%
“…To this end, a few studies managed to reduce nanosheet lateral size from microns to nanometers by strong sonication, filtration, and controlled suspension freezing . It was reported that short‐term sonication (20 min) would shorten GO flakes by a factor of 7 and correspondingly doubled water flux in resultant membranes . Faster ion permeation was also observed in GO laminates stacked by short‐sized nanosheets .…”
Section: Transport‐controlling Effectsmentioning
confidence: 99%
“…These results agree with the marginal presence of oxygen functionalities, which can also act as architectural spacers between the graphene flakes. 190 It is noteworthy that both theoretical and experimental studies previously reported that R6G molecules can reduce graphene flakes by removing oxygen functionalities, including epoxy, hydroxyl and carbonyl groups possibly formed in the defective regions of the graphene flakes. 148 Adhesion force measurements were carried out with an AFM 191,192 in humid (relative humidity -RH -B75%) ambient air (assuming the Lennard-Jones force-separation relation 193,194 ) to effectively identify the water accessible sites of the R6G-FG membrane.…”
Section: Fabrication and Morphological Characterization Of Graphenebamentioning
confidence: 99%
“…Myriad studies have already investigated the biological effects of GO on cells, tissues, and animals assuming inhalation or intravenous administration as the most plausible human exposure routes. [16][17][18] At the same time, its application in food packaging, [12] water filtration, [19] nanomedicine, [20] and the general potential of carbon-based ENMs in agriculture [21] suggest that ingestion is another possible route for human exposure to GO. Interestingly, there have only been a handful of studies to explore the toxicodynamics of ingested GO on human intestinal epithelial cells [22][23][24][25][26] and even fewer in vivo studies of its system-wide effects upon oral administration.…”
Section: Introductionmentioning
confidence: 99%